2023
DOI: 10.3390/antiox12122103
|View full text |Cite
|
Sign up to set email alerts
|

Food Polyphenols as Preventive Medicine

Joseph Kanner

Abstract: Reactive oxygen species (ROS) are the initiators in foods and in the stomach of oxidized dietary lipids, proteins, and lipid-oxidation end-products (ALEs), inducing in humans the development of several chronic diseases and cancer. Epidemiological, human clinical and animal studies supported the role of dietary polyphenols and derivatives in prevention of development of such chronic diseases. There is much evidence that polyphenols/derivatives at the right timing and concentration, which is critical, acts mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 250 publications
0
5
0
Order By: Relevance
“…Thus, it is logical to assume that the concentrations of resveratrol required would be lower in cancer cells compared to normal cells, owing to the elevated levels of intracellular copper in cancer cells. Multiple studies [45][46][47][48] and this study have demonstrated the cytotoxic effects of lower quantities of resveratrol on cancer cells. To further establish this phenomenon, non-tumorigenic epithelial MCF-10A cells are cultured with copper enrichment to replicate the copper state of cancer cells in the body.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, it is logical to assume that the concentrations of resveratrol required would be lower in cancer cells compared to normal cells, owing to the elevated levels of intracellular copper in cancer cells. Multiple studies [45][46][47][48] and this study have demonstrated the cytotoxic effects of lower quantities of resveratrol on cancer cells. To further establish this phenomenon, non-tumorigenic epithelial MCF-10A cells are cultured with copper enrichment to replicate the copper state of cancer cells in the body.…”
Section: Discussionmentioning
confidence: 61%
“…Sodium alginate itself also has a certain antioxidant effect; research showed that in a certain mass concentration range, sodium alginate solution could show good antioxidant effects [32]. The scavenging rate on H 2 O 2 by sodium alginate was higher than the scavenging on DPPH radicals, and the strong oxidizing properties of H 2 O 2 may have damaged its molecular structure [33]. Overall, both BBH and BBH-L-Gel have good antioxidant properties, and they complement each other and are suitable for the treatment of skin diseases in a state of inflammation such as eczema.…”
Section: Results Of Antioxidant Activity Of Bbh-l-gelmentioning
confidence: 99%
“…Polyphenols can act synergically in the gut and bloodstream against various biotic and abiotic stressors [126]. Studies support the preventive role of polyphenols in the fight against diseases [127], free radicals, gut health [128], and cholesterol oxidation products [129], among others.…”
Section: Wellbeing and Prevention Through Nutritionmentioning
confidence: 98%